Predicting the Impact of Commercialization Factors on the Social Mission of Islamic Microfinance Institutions for Muslim Communities - Hesi Eka Puteri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This study examines the impact of commercialization factors, covering profitability, regulation, and competition, on the social performance of Islamic rural banks that cater specifically to the Muslim community.Â As a community banking institution operating by Islamic principles, Islamic rural banks are faced with two performance targets, namely financial performance and social performance, both of which are interrelated. This study is quantitative research based on a survey on six units of Islamic rural banks in West Sumatra. Data from the financial services authority and other financial documents at Islamic rural banks are analyzed with panel data regression. The findings of this research show that profitability and competition influence social performance. Meanwhile, there is no regulationâ€™s impact on social performance.Â Regulatory factors that were initially expected to strengthen the social responsibility mission of Islamic rural banks did not stimulate the increase of social performance. This study reveals the importance of the commercialization factor in improving the social performance of Islamic rural banks which aims at increasing the social benefits for the low-income Muslim community.Penelitian ini bertujuan untuk menguji dampak dari faktor-faktor komersialisasi yang meliputi profitabilitas, regulasi dan kompetisi terhadap kinerja sosial BPR Syariah khususnya kepada penggunanya yaitu masyarakat Muslim. Sebagai sebuah community banking yang beroperasi dalam prinsip-prinsip Islam, BPR Syariah dihadapkan pada dua target kinerja yaitu kinerja keuangan dan kinerja sosial yang keduanya saling terkait. Penelitian ini menggunakan pendekatan kuantitatif berdasarkan survei pada enam unit BPR Syariah di provinsi Sumatera Barat, Data dikumpulkan dari Otoritas Jasa Keuangan dan dokumen di BPR Syariah kemudian dianalisis dengan regresi data panel. Hasil penelitian ini menunjukkan bahwa profitabilitas dan persaingan berpengaruh terhadap kinerja sosial, sedangkan regulasi tidak berpengaruh terhadap kinerja sosial. Faktor regulasi yang semula diharapkan memperkuat misi tanggung jawab sosial BPR syariah, ternyata tidak merangsang peningkatan kinerja sosial. Studi ini mengungkap akan pentingnya faktor komersialisasi dalam meningkatkan kinerja sosial BPR syariah dengan meningkatkan manfaat sosial untuk masyarakat Muslim berpenghasilan rendah.